2013
DOI: 10.1186/2049-1891-4-43
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of genes that control fat deposition in chickens

Abstract: BackgroundFat deposits in chickens contribute significantly to meat quality attributes such as juiciness, flavor, taste and other organoleptic properties. The quantity of fat deposited increases faster and earlier in the fast-growing chickens than in slow-growing chickens. In this study, Affymetrix Genechip® Chicken Genome Arrays 32773 transcripts were used to compare gene expression profiles in liver and hypothalamus tissues of fast-growing and slow-growing chicken at 8 wk of age. Real-time RT-PCR was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(76 citation statements)
references
References 51 publications
4
64
0
Order By: Relevance
“…It was found that the ELOVL6 promoter region has a QTL polymorphism site that can regulate the composition of porcine fatty acid [37]. Studies in poultry have found that single nucleotide polymorphisms in the ELOVL6 gene are associated with the deposition of subcutaneous fat [38]. SQLE located on the endoplasmic reticulum is the first oxygenation step in the biosynthesis of sterols and is considered to be one of the key enzymes in this pathway, which has an important impact on the flux synthesis of cholesterol [39].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the ELOVL6 promoter region has a QTL polymorphism site that can regulate the composition of porcine fatty acid [37]. Studies in poultry have found that single nucleotide polymorphisms in the ELOVL6 gene are associated with the deposition of subcutaneous fat [38]. SQLE located on the endoplasmic reticulum is the first oxygenation step in the biosynthesis of sterols and is considered to be one of the key enzymes in this pathway, which has an important impact on the flux synthesis of cholesterol [39].…”
Section: Discussionmentioning
confidence: 99%
“…Another 8 birds from XH and WRR (n = 4 per population) were used to confirm miR-16 expression pattern. In our previous study, liver tissues from 3 indigenous XH and 3 commercial WRR chicken at about 7-weeks-old were used for mRNA microarray analysis31. QY and XH chicken are populations with similar growth performance, and thus used to represent populations with the same general growth characteristics and to contrast with fast-growing WRR.…”
Section: Methodsmentioning
confidence: 99%
“…After data normalization, significance was determined by ANOVA analysis and false-positive reduction ( p  < 0.01). mRNA expression was based on our previous microarray data31. The microarray dataset was deposited to Gene Expression Omnibus (GEO) under accession number GSE80580.…”
Section: Methodsmentioning
confidence: 99%
“…In cattle, the gene expression abundances of LPL , as well as FASN , exhibited significant positive correlations with IMF content in the longissimus dorsi muscle (Jeong, Kwon, Im, Seo, & Baik, ). In chicken, the expression of LPL was up‐regulated in fast‐growing chickens than slow‐growing chickens (Claire D'Andre et al., ). Compared with the WK squabs, the expressions of LPL in both liver and breast muscle were consistently elevated in the SQ squabs, which indicated that the phenotypic differences in terms of IMF content between the two pigeon breeds may result from the significant up‐regulation of genes involved in the lipogenic process.…”
Section: Discussionmentioning
confidence: 99%